PEREMPUAN BERPENDIDIKAN TINGGI DI TUBAN: ANTARA HUKUM DAN REALITA - Siti Fatimah; Irma Rosyida (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2021)
This study to describe woman with hingher education in review of law and reality in Tuban East Jawa. In this modern era, women with higher education still experience gender discrimination against their nature and it is not uncommon to find gender stereotypes about the unimportance of hingher education for a woman by community. This study is qualitative research with a descriptive method. This type of research is included in a case study. In collecting data, using the interview, observation and documentation methods. The research subjects consisted of woman with higher education and careers, housewives with higher education, husbends, childern of spouses with highly educated perents, and female students who were pursuing higher education at Tuban. The resulth show that education in Islamic law is is obligatory for every Muslim, including woman. Modern-day woman with higher education for woman are an important need, with the hope that their knowladge and knoeledge are as a provision for woman to become mother as good educators for their children, besides that woman can show their existence as qualified servants of God in front of humans, especially before Allah SWT. The reality is that woman with higher education still have a lot of gender discrimination and gender stereotypes in society. Women are still seen as household managers, so that education for them is secondary and even neglected.